Identifying Functional Mechanisms in Psychotherapy: A Scoping Systematic Review - Carey, Timothy A.; Griffiths, Robert; Dixon, James E.; Hines, Sonia (Frontiers in Psychiatry, 2020)
The identification of fundamental mechanisms is an important scientific pursuit in many fields of enquiry. With regard to the development of psychological treatments, understanding the mechanisms through which change occurs such that psychological distress resolves, can enable us to develop more effective and efficient interventions. In the field of psychotherapy, mechanisms are often identified either statistically or conceptually. The most powerful and useful mechanisms, however, are functional rather than statistical or conceptual. More specifically, with regard to mechanisms relevant to psychotherapy, it is difficult to identify what any of these mechanisms actually do in a mechanistic sense. That is, the mechanics of putative mechanisms are generally unspecified. In order to obtain a rigorous and comprehensive account of the current mechanisms in psychotherapy, as well as to evaluate their usefulness, a systematic scoping review was conducted. The systematic scoping review did not yield any mechanisms that were expressed in functional terms. We argue that, in order for psychotherapy to improve its effectiveness and efficiency, the standard for what is accepted as a useful mechanism needs to be substantially raised. Only functional mechanisms that express plausible actions consistent with known biological processes should be used to inform therapeutic interventions.